Dorsal Augmentation-Diced Cartilage Techniques: The Diced Cartilage Glue Graft - Tasman, Abel-Jan (Facial Plastic Surgery, 2017)
The quest for the ideal method for augmenting the nasal dorsum continues to be a matter of debate, with both most surgeons and patients preferring autologous tissue. This article reviews the current use of diced cartilage for nasal augmentation, emphasizing the diced cartilage in fibrin glue (DCG) graft. It offers the first collation of unfavorable outcomes and complications of the DCG graft seen in a series of 108 patients treated at the author's institution. The DCG graft continues to be a versatile graft that is stable over time and combines unique features. It has proved to be particularly well suited for segmental augmentations of the dorsum. Resorption of the graft has been rare and infrequent unfavorable outcomes have all been amenable to successful minor surgical revisions.
Keywords: rhinoplasty; dorsal augmentation; diced cartilage; fibrin glue